“They fell through the cracks:” caregiver perspectives on the difficulties of COVID-19 implementation transitions for children and youth with special healthcare needs (CYSHCN) - Smith, D. Grace; Cancilliere, Mary Kathryn; Hayes, Tara M.; Elwy, Anashua Rani; Sarkar, Indra Neil (Frontiers in Pediatrics, 2025)
IntroductionThe COVID-19 virus and its relevant prevention protocol had significant impacts on children and youth with special healthcare needs (CYSHCN), including those with physical, intellectual, and developmental disabilities. Previous studies have examined the first year of the pandemic, identifying the implications of social distancing, remote services/education, and masking and testing protocol on the mental, physical, and developmental well-being of this population.ObjectivesWe focus on moments of transition, when vaccines were disseminated and mandates/resources removed. By identifying how protocol and interventions in these moments included, neglected, or negatively impacted CYSHCN, we can inform more inclusive, safe, and equitable decision-making in future health crises.MethodsWe report the transition-moment-related reflections of fourteen focus groups conducted among caregivers (including parents) of CYSHCN between March and December of 2022 (n = 77). Focus groups were conducted in close partnership with a local non-profit organization, and facilitation protocol were co-developed by community leaders in the CYSHCN area. Focus groups were recorded, transcribed, and analyzed using directed content analysis and thematic analysis, guided by implementation science theories on interventions’ relative dis/advantages and perceived adaptability.ResultsCaregivers provided transition-moment reflections of how the timing, support, and in/flexibility of pandemic intervention implementation and de-implementation negatively impacted their CYSHCN. We generated three themes to describe these views: (1) “Our kiddos didn’t have a plan when this happened:” Lack of transition support into isolation meant loss of necessary structures and services; (2) “He couldn’t comprehend:” Transition communication, particularly surrounding mandates and protocol, was not handled well for CYSHCN; and (3) “Listen, we’re still in the middle of pandemic:” Transition timing neglected consideration of CYSHCN.DiscussionCYSHCN needs were neglected in the pandemic’s transition moments, creating significant implications for their mental/emotional, physical, and cognitive/developmental well-being. Reflecting these findings, and particularly facets that extend established literature, we urge inclusive research and policy models, empowering members of the CYSHCN community as leaders in knowledge and protocol production, particularly when considering the adaptability and relative advantage of interventions. Such models are crucial in developing messaging around pandemic policies, creating infrastructural support for flexibility, and adding supports and delays when de-implementing mandates.